Characteristics and Origin of Rock Glaciers in Northern Tien Shan (Kazakhstan/Kyrgyzstan) - Bolch, Tobias; Gorbunov, Aldar P. (Permafrost and Periglacial Processes, 2014)
Northern Tien Shan is characterised by a distinct periglacial belt that contains many rock glaciers with an area of 1km 2 or more. To investigate the reason for their large size and variable occurrence, we analysed a representative subsample of the rock glaciers with respect to topographic and climatic variables. A simple permafrost model indicates that the rock glaciers originate in the zone where permafrost occurrence is very likely and some large rock glaciers flow down to elevations where permafrost is unlikely to exist outside the rock glaciers themselves. Correlation and multiple regression analyses revealed that the occurrence and characteristics of the rock glaciers can only be partly explained by the characteristics of the contributing area (e.g. its area or the headwall height). The correlation is greater with talus-type rock glaciers than with moraine-type rock glaciers. The climate can explain the general occurrence of rock glaciers but not their specific characteristics. It is hypothesised that the main reason for the specific distribution and characteristics of these large rock glaciers relates to the interaction with polythermal glaciers, topographic characteristics, intensive weathering and rock avalanches triggered by seismic activity. Copyright